Impact of industry 4.0 on companies: Value chain model analysis - Lucia Kohnová; Nikola Salajová (Administrative Sciences, 2023)
Although the concept of Industry 4.0 is newer, more and more companies are responding to this concept and incorporating it into their business models. Industry 4.0 arose as a result of the development of new technologies based on automation, through which technologies can communicate with each other. The aim of this study is to analyze the impact of Industry 4.0 on companies from the point of view of the value chain model. The study points out why the model is a suitable tool for evaluating changes. The research consisted of 1164 respondents, while the sample consisted of 591 Czech companies and 573 Slovak companies. We found that 62% of companies carry out activities in the field of robotization and automation to a large extent, and 32% carry out these activities little or not at all. Regarding the impact of Industry 4.0 on individual activities in the value chain, we found that companies expect the greatest impact on technological development (secondary activity) and customer service (primary activity). On the contrary, they least expect the impact of Industry 4.0 in the primary activities of input logistics and operation. From this point of view, we can say that companies perceive the impact of Industry 4.0 on the activities taking place in their value chains. However, it is important to capture these changes, react appropriately to them and remain competitive.
Keywords: 350; digitalization; Industry 4.0; technology; value chain